Exploring prevalent injuries among tennis players and optimal rehabilitation approaches: A systematic review protocol. - Eva María Rodríguez-González; María Soledad Amor-Salamanca; Domingo Rosselló; María de Lluc-Bauza; Francisco Hermosilla-Perona; Adrián Martín-Castellanos; Ivan Herrera-Peco (PLoS ONE)
Introduction Tennis is a globally popular sport known for its numerous health benefits. However, it also underscores the physical demands and potential injuries associated with high-performance play. This review emphasizes the role of kinetic chains in executing powerful movements and discusses common injuries, particularly in the upper limbs due to the sport's overhead nature. It highlights the importance of effective rehabilitation methods for swift recovery and long-term performance enhancement in high-performance tennis players. Aims The review aims to investigate the relationship between age, sex, and injury prevalence among high-performance tennis players to inform injury prevention strategies. Methodology This review protocol will provide a description on effective rehabilitation methods to tennis players, aiding coaches, physiotherapists and physicians. Methodologically, this systematic review will develop following the PRISMA guidelines, focusing on articles published between 2011 and 2024, with eligibility criteria specified. Data collection involved screening titles and abstracts, removing duplicates, and assessing full texts for eligibility. Data extraction will include information on authors, publication year, evidence level, participant demographics, injuries, treatments, etc. The GRADE framework will be used for evidence quality assessment, and NIH criteria were applied for study quality assessment. Trial registration Prospero registration number: CRD42023453182.